Understanding travel expenditure pattern using CHAID method: a study of domestic and international tourists in UNESCO world heritage city of Melaka, Malaysia. - Ab Rahman, Syakir Amir; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor (GATR Enterprise, 2014)
Tourism has long been known as a tool for economic development due to its capability and strength to provide economic sources from host destination. This study examined the tourists’ expenditure pattern in Melaka city. Diary record survey was conducted at three different groups of selected hotels based on stars ratings- 5 & 4 stars hotel; 3,2 & 1 stars hotel; and budget hotels. A total of 1500 survey booklets were distributed, only 1000 surveys were collected. Chi-squared Automatic Interaction Detection (CHAID) was used to model interaction of domestic and international tourists in five tourism sectors-accommodation, food and beverages, transportation, entertainment and shopping. Results revealed that the tourists spent less in transportation (RM22.50 and below) and entertainment (RM22.50 and below), and heavily spent in other three sectors, shopping (RM475 and below), accommodation (RM700 and below), food and beverages (RM367 and below). It is expected that modeling of the pattern and distribution of these expenditure will assist the relevant authorities in geographical visitation patterns, economic impacts and decision making.